Characterization and toxicological evaluation of leachate from closed sanitary landfill - Emenike, C.U. (2012)
Landfilling is a major option in waste management hierarchy in developing nations. It generates leachate, which has the potential of polluting watercourses. This study analysed the physico-chemical components of leachate from a closed sanitary landfill in Malaysia, in relation to evaluating the toxicological impact on fish species namely Pangasius sutchi S., 1878 and Clarias batrachus L., 1758. The leachate samples were taken from Air Hitam Sanitary Landfill (AHSL) and the static method of acute toxicity testing was experimented on both fish species at different leachate concentrations. Each fish had an average of 1.3 +/- 0.2 g wet weight and length of 5.0 +/- 0.1 cm. Histology of the fishes was examined by analysing the gills of the response (dead) group, using the Harris haemtoxylin and eosin (H&E) method. Finneys' Probit method was utilized as a statistical tool to evaluate the data from the fish test. The physico-chemical analysis of the leachate recorded pH 8.2 +/- 0.3, biochemical oxygen demand 3500 +/- 125 mg L-1, COD 10 234 +/- 175 mg L-1, ammonical nitrogen of 880 +/- 74 mg L-1, benzene 0.22 +/- 0.1 mg L-1 and toluene 1.2 +/- 0.4 mg L-1. The 50% lethality concentration (LC50) values calculated after 96 h exposure were 3.2% (v/v) and 5.9% (v/v) of raw leachate on P. sutchi and C. batrachus, respectively. The H&E staining showed denaturation of the nucleus and cytoplasm of the gills of the response groups. Leachate from the sanitary landfill was toxic to both fish species. The P. sutchi and C. batrachus may be used as indicator organisms for leachate pollution in water.